Student Earnings Expectations: Heterogeneity or Noise? - Luis Diaz-Serrano; Joop Hartog; William Nilsson; Hans van Ophem; Po Yang (Center for Economic Studies and ifo Institute (CESifo), 2016)
Students' choices in education can only be based on expected outcomes. Econometric models that infer expectations based on ex post outcomes impose a rational structure of expectations on school performance and post-graduation earnings. Direct surveys suggest much ignorance and fuzziness. We use survey data on expectations in four universities in three countries and check for relations of expected probability to graduate and of expected earnings with personal abilities and attitudes. We find that most of the difference in expectations among individuals is just noise.
Keywords: I21; I26; J24; D83; 330; student expectations; earnings; earnings dispersion; risk attitudes